The Long-Run and Gender-Equalizing Impacts of School Access : Evidence from the First Indochina War - Dang, Hai-Anh H.; Hoang, Trung X.; Nguyen, Ha (World Bank, Washington, DC, 2018)
Very few studies currently exist on the long-term impacts of schooling policies in developing countries. This paper examines the impacts -- half a century later -- of a mass education program conducted by the Democratic Republic of Vietnam in the occupied areas during the First Indochina War. Difference-in-difference estimation results suggest that school-age children who were exposed to the program obtained significantly higher levels of education than their peers who were residing in French-occupied areas. The impacts are statistically significant for school-age girls and not for school-age boys. The analysis finds beneficial spillover and inter-generational impacts of education: affected girls enjoyed higher household living standards, had more educated spouses, and raised more educated children. The paper discusses various robustness checks and extensions that support these findings.